New Muslim Converts Experience in Embracing Islam: An Analysis of the Pre Conversion, Conversion and Post Conversion Phases - Nuradli Ridzwan Shah Mohd Dali; Azman Ab. Rahman; Irwan Mohd Subri; Mahazan Abdul Mutalib @ Talib; Wan Mohd Fazrul Azdi Wan Razali; Rose Irnawaty, Ibrahim; Norlina, Ismail (Islamic Cultural Centre, London., 2024)
Non-Indexed Publication